Social carry-over effects underpin trans-seasonally linked structure in a wild bird population - Firth, J; Sheldon, B (John Wiley & Sons, Inc., 2016)
Spatial structure underpins numerous population processes by determining the environment individuals experience and which other individuals they encounter. Yet, how the social landscape influences individuals’ spatial decisions remains largely unexplored. Wild great tits (